EFFECT OF NANDA-I, NIC, AND NOC DOCUMENTATION SYSTEM TRAINING ON QUALITY OF NURSING CARE DOCUMENTATION IN THE PERINATAL WARD OF YOGYAKARTA REGIONAL PUBLIC HOSPITAL - Enny Eko Setyaningrum; Intansari Nurjannah; Anik Rustiyaningsih (Belitung Nursing Journal, 2019)
Background: The existing standard of nursing language consists of NANDA-I for diagnostic language standard, Nursing Intervention Classification (NIC) for nursing intervention, and Nursing Outcome Classification (NOC) for nursing outcomes. One way to improve the quality of nursing care documentation is to provide training in the documentation system. Objectives: To determine the effect of providing NANDA-I, NIC, and NOC (NNN) nursing care documentation systems training on the quality of nursing documentation. Methods: This was a pre-experimental study with pretest posttest design without a control group. Twenty-one nurses and eighty-six Medical Records (MR) of patients who were treated in the perinatal ward of Yogyakarta Regional Public Hospital were used as samples selected using purposive sampling. Those nurses were trained in the nursing care documentation system. The quality of nursing care documentation was measured using modified Quality of Diagnoses, Interventions and Outcomes (Q-DIO) instrument. Data were analyzed using Independent samples t-test with a confidence level of 95%. Results: The average of the scores of the quality of nursing documentation before training was lower (1.91) than the average after training (2.78). There was a significant difference in the quality of nursing documentation before and after training (p < 0.001). Conclusion: Training of NNN nursing documentation system could improve the quality of nursing documentation in the perinatal ward of Yogyakarta Regional Public Hospital.